Examining the Mindsets of Primary School Teachers and University Students from Literacy Volunteer Community - Utami, Dita Rezkia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The importance of implementing a growth mindset in the education sector has called for all actors to develop growth mindset. This study investigated the mindsets of primary school teachers and university students from the Literacy Volunteer Community in Sumbawa Regency (West Nusa Tenggara, Indonesia) prior to the teaching of growth mindset. A descriptive quantitative approach was used, with an online survey to assess participants' familiarity with the concepts of growth and fixed mindsets, their mindset level, and their views regarding growth mindset and fixed mindset attributes. The findings showed that more than half of the volunteers (55%) were not well-familiarized with the mindsets' concepts and (52%) had a mixed mindset with a fixed mindset orientation. The mixed mindset results reveal a complex view of the volunteers on the mindsets' attributes. The implications of these findings suggest that there is a need for more training on growth mindset for actors across the education sector to promote better learning and academic achievement among students.